Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T00:05:42+01:00
7a+c=d => 7a=d-c => a=(d-c)/7

(a+b)*h=c => a+b=c/h => a=c/h-b

(2+a)*c=1 => c=1/(2+a)

l+mn=m => l=m-mn => l=m(1-n)

l+mn=m => l=m-mn => l=m(1-n) => m=1/(1-n)

2cde-cd-d=0 => d(2ce-c-1)=0 => 2ce-c-1=0 => 2ce-c=1 => c(2e-1)=1 =>2e-1=1/c => 2e=1/c+1 => e= 1/2c+1/2

a+b=c => b=c-a

2b+2c=d => 2c=d-2b => c=d/2-b

g+hg=1 => g(h+1)=1 => g=1/(h+1)

g+hg=1 => hg=1-g => h=1/g-g/g => h=1/g-1

7a+c=d => c=d-7a

5c²+d=c => d=c-5c²

2ab+bc=1 => b(2a+c)=1 => b=1/(2a+c)

2g(1+c)=c => g=c/2*(1+c)

2g(1+c)=c => 2g+2gc-c=0 => c(2g-1)=-2g => c=-2g/(2g-1) => c=2g/(1-2g)